Regional Revenue and Expenditures Budget Transparency in the Context of Regional Financial Law - Eka Pala Suryana (Unnes Law Journal, 2020)
This research aims to describe the transparency of the use of the Semarang City Regional Revenue and Expenditure Budget and discover the forms, mechanisms and constraints in obtaining transparency of information on the use of the Semarang City Revenue and Expenditure Budget, this research uses a sociological juridical research type approach method, by using primary data and secondary data which are then analyzed using qualitative data analysis.The results of the study can be seen that the transparency of the use of the Semarang City Regional Revenue and Expenditure Budget already has internal regulations in the form of Mayor Regulation number 26 of 2012 and forms and mechanisms in accordance with Law number 14 of 2008 although internal and external obstacles are still found that result implementation is less than optimal so that it inhibits the realization of good governance (good governance). The conclusions from the results of the study show that the transparency of the use of the Semarang City Regional Revenue and Expenditure Budget is in accordance with Law number 14 of 2008 and already has forms and internal mechanisms, although in the implementation phase there are still obstacles both internally and externally.